Association between social-cognitive factors and intention towards sexual activity among schoolgoing late adolescents in Kuantan, Malaysia - Abdullah, Fa’iza; A. Rahman, Nor Azlina; Muhammad, Noor Azimah; Zainuddin, Nur Akmanidar; Samsudin, Suhaiza (Taylor & Francis Online, 2020)
This was a cross-sectional study to identify the association between sociocognitive factors (permissive attitude, social-norms, and self-efficacy) and intention towards sexual activity among 466 Malaysian school-going late adolescents (aged 18–19 years) in Kuantan, Malaysia. Majority were females (64.4%), Malays (67.4%) and Muslims (68.2%). Simple logistic regression from data collected by self-administered validated Youth Sexual-Intention Questionnaire (YSI-Q) showed significantly increase risk of having sexual intention for each unit increase in permissive attitude, social-norms and self-efficacy scores with the odds ratio (OR) of 1.424, 1.303 and 1.215, respectively. On the other hand, multivariate logistic regression resulted in male, non-Malay, ever-smoker students and permissive attitude showing significantly higher risk towards having sexual intention with the OR of 0.163 (male was the reference group), 5.110, 3.288 and 1.236, respectively. In order to reduce risky sexual behaviour among adolescents, school-based health education is essential.